The Use of Automation in Rail Transport to Ensure Interchanges in Regional Passenger Transport - Kučera, Petr; Heřmánková, Andrea (EDIS - vydavateľstvo Žilinskej univerzity, 2024)
This paper deals with the use of automation in rail transport to provide transfer links in public passenger transport. The methods of railway transport management in the Czech Republic are presented and their suitability for the use of automation in regional passenger transport is assessed. The authors consider the impact of automation only from a technological point of view. In this paper, the authors propose a modification of the train departure using a layout criterion and time stops to provide transfer links using the Automatic Route Setting System. The authors consider the use of the Real Time Rescheduling considering the traffic on the railway line, as well as the traffic connections of the public line transport. The paper proposes the use of automation software to improve the quality of public passenger transport.
Využití automatizace v železniční dopravě k zajištění návazností v regionální osobní dopravě
Keywords: automatic route setting system; time stop; layout criterion; transfer links; regional public transport; automatické stavění vlakových cest; časová zarážka; dispoziční kritéria; přestupní vazby; regionální osobní doprava